VARIABILITAS KONSUMSI PANGAN PADA MASYARAKAT NUSA TENGGARA TIMUR - Bernard B de Rosari; Sri Widodo; Masyhuri Masyhuri (Agro Ekonomi, 2001)
The analysis intended to identify the various food consumption of the people of East Nusa Tenggara is carried out by using the data from Susenas in East Nusa Tenggara Province in 1996. There are 500 households included in the analysis those are classified according to income level (low, middle, high) and residence (rural, urban).The estimation of the consumption function is using Maximum Likelihood Method (MLE). Results of the analysis reveals that expenditure allocation for foodstuffs is 63% and 37% for non-foodstuffs. High-income people combine rice and corn to meet their carbohydrate needs while low-income people rely on corn. Protein sources including fish and meat are not affordable by the people of East Nusa Tenggara